Analisis Pengaruh Penggunaan Serbuk Limbah Glasswool pada Campuran Plesteran Untuk Meningkatkan Kekedapan Suara - M. Astu Narendra Kusuma; Rizqi Fajar Ekananda; Shifa Fauziyah; Asri Nurdiana (Universitas Diponegoro, 2024)
Noise pollution is a nuisance to the environment caused by sound or sound which causes unrest in the living things around it. According to the World Health Organization (WHO), noise levels above 85 dB with exposure for more than 8 hours are hazardous to health. When excessive, noise pollution can lead to increased stress, sleep disturbances, and even hearing damage. the result of this feeling of stress also affects mental health, for example, more irritable, anxious, frustrated, etc. Not only adults, children are also very vulnerable to the negative effects of this noise pollution. Based on this, an innovation emerged that could be a solution, namely the use of glasswool in plaster mixes to improve soundproofing. The purpose of this research is to increase the level of soundproofing in a room. In this study, the experimental method will be used with the addition of glasswool to the stucco mixture with a variation of the addition of 20% glasswool from cement with a total of 12 specimens. Test object in the form of a cube measuring 15 cm x 15 cm to test the compressive strength of concrete and a modified cube measuring 25 cm x 25 cm to test soundproofing, and a compressive strength test was carried out at the age of +-7 days. It is hoped that by conducting this research noise pollution can be reduced every year, and can achieve compressive strength that meets SNI 03-2837-2002.